Effect of elevated temperature on flexural behavior and fibers-matrix bonding of recycled PP fiber-reinforced cementitious composite. (1st February 2021) - Francioso, Vito; Moro, Carlos; Castillo, Alberto; Velay-Lizancos, Mirian
Highlights: Recycled PP fibers mitigate the flexural strength loss caused by thermal shock. Fibers provided mortars a residual strength and ductile behavior after peak-load. High temperature exposure and slow cooling enhance this positive effects of fibers. Plastic fibers penetrate into the pores network after 200 °C exposure. Fiber-matrix bonding of mortars is positively affected by exposure up to 200 °C. Abstract: This research aims to study the effects of elevated temperature exposure on the flexural performance of recycled polypropylene (PP) fiber-reinforced cementitious composites. Four mixtures with different percentages of PP fibers (0%, 0.5%, 1%, and 1.5% by volume) were studied. For each mortar, 9 samples of 40 × 40 × 160 mm were cast and cured for 28 days. While 3 samples of each mixture were tested under standard conditions, the other 6 were exposed to high temperature (200 °C) for 2 h and cooled in two different ways before testing (3 were tested hot and 3 were let cool down completely). Flexural strength test, Differential Image Correlation (DIC) and digital microscopy techniques were employed to evaluate the effects of high-temperature exposure and cooling procedures on flexural strength, toughness and bonding. Results showed that the use of recycled PP fibers had a negligible effect on flexural strength in normal conditions. However, fibers provided mortars a residual strength and ductile behavior after peak-load. Besides, flexural strength, post-peak residual strength, secondary strength and secondary toughness were enhanced after exposure to 200 °C and slow cooling, improving the behavior of the composite under flexural stresses. These results, along with the optical microscope images, suggest an improved bonding between the mortar matrix and the PP recycled fibers after exposure to 200 °C (temperature close to the melting point of fibers).